(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The article discusses the possibilities of using a crowdfunding platform for the development of women’s human capital in Uzbekistan, as well as the percentage of women among students of educational institutions in Uzbekistan, the gender gap among the unemployed in Uzbekistan, and also studied the types of entrepreneurship led by women in various industries in Uzbekistan.